Insights into Bactericera cockerelli and Candidatus Liberibacter solanacearum interaction: a tissue-specific transcriptomic approach - Singh Rajkumar, Mohan; Ibanez-Carrasco, Freddy; Avila, Carlos A.; Mandadi, Kranthi K. (Frontiers in Plant Science, 2024)
The tomato-potato psyllid, Bactericera cockerelli (Šulc), belonging to the Hemiptera order, is an insect pest of solanaceous crops and vectors a fastidious bacterium, Candidatus Liberibacter solanacearum (CLso), the presumptive causal agent of zebra chip and vein greening diseases in potatoes and tomatoes, respectively. The genome of B. cockerelli has been sequenced recently, providing new avenues to elucidate mechanistic insights into pathogenesis in vegetable crops. In this study, we performed RNA-sequencing of the critical psyllid organs (salivary glands and ovaries) involved in CLso pathology and transmission to host plants. Transcriptome analysis revealed differentially expressed genes and organ-specific enrichment of gene ontology (GO) terms related to metabolic processes, response to stress/stimulus, phagocytosis, proteolysis, endocytosis, and provided candidate genes encoding transcription factors (TFs). To examine gene regulatory networks across the psyllid organs under CLso(-) and CLso(+) conditions, we performed weighted gene co-expression network analysis (WGCNA), and unique modules differentiating the psyllid organs were identified. A comparative GO analysis of the unique gene modules revealed functional terms enriched in response to stress, gene regulation, and cell division processes in the ovaries. In contrast, respiration, transport, and neuronal transmission-related GO terms were enriched in the salivary glands. Altogether, this study reveals new insights into tissuespecific expression of the psyllid organs in the absence or presence of CLso bacterium. This knowledge can be leveraged to develop new pest and disease management strategies by delineating the regulatory networks involved in the psyllid-CLso interaction.